Diseño de vivienda progresiva con estrategias sostenibles para el barrio Cristal Bajo de Bucaramanga-Colombia - Quintero González, Walkyria Alejandra (Universidad Antonio Nariño, 2022)
Through this final project, the theoretical-practical approach of progressiveness turns into a solution for different qualitative and quantitative housing problems based on a replicable architectonical model design in the neighborhood Cristal Bajo located in Bucaramanga, Santander.